Public Policy and Policy-Making - Yalmanov, N. (KnE Social Sciences, 2021)
This research adopts a methodological approach to the analysis of policy-making, which allows both a comprehensive study of policy-making and also helps to determine the content of public policy. The research, firstly, critically reviews the popular political science conceptual models of policy-making to determine factors that make the existing models unfit to explain the essence and fundamental attributes of this process. Then, the main characteristics of political decisions based on the normative approach will be highlighted and the key features of this mechanism will be determined. Policy decisions features considered in the context of political science are interconnected. Key features such as political power, interests, responsibility and rationality lead to a conclusion about the preventive nature of political decisions. The preventive orientation of political actions means the intention to create, direct and control events distant in the time continuum in the right way, anticipating undesirable effects in the exercise of power capability. The normative approach to study of policy-making creates a methodological basis for determination of public policy and shows that public policy is the definition of strategic goals for the development and consolidation of society, through activities related to the development of a political course for the society development and integration through policy-making. Keywords: public policy, policy-making, theory of policy-making, rationality